Effects of Project-Based Learning on Critical Thinking Skills of Fourth-Grade Students - Hadistia, Pipih; Darmini, Mimin; Sati, Sati (Papanda Publisher, 2025)
Critical thinking skills represent essential competencies for 21st-century education, yet Indonesian elementary students consistently demonstrate limited analytical capabilities. Project-Based Learning (PBL) offers a constructivist approach that potentially addresses these deficiencies through authentic, collaborative problem-solving experiences. This study investigated PBL's effectiveness in enhancing fourth-grade students' critical thinking skills within integrated science education. A pre-experimental One Group Pretest-Posttest Design was employed with 25 fourth-grade students at SD Negeri 1 Watubelah, Cirebon Regency. The intervention implemented six PBL steps over three weeks focusing on magnetism concepts. Critical thinking skills were assessed using a validated 20-item test based on Archer's indicators (validity coefficients 0.65-0.82, reliability α = 0.87). Data analysis included paired t-tests and normalized gain calculations, complemented by qualitative observations of student engagement. Significant improvements were observed from pretest (M = 27.8, SD = 9.2) to posttest (M = 91.2, SD = 6.4) with t = 21.18 (p < 0.001). The normalized gain of 0.87 indicated high practical significance according to Hake's criteria. Qualitative observations revealed enhanced student participation, collaborative skills, autonomous learning behaviors, and communication abilities. Students transitioned from passive recipients to active problem-solvers demonstrating analytical thinking and creative solution development. Project-Based Learning significantly enhances critical thinking skills among fourth-grade students in science education contexts. The substantial effect size validates PBL as an effective alternative to traditional teacher-centered instruction in Indonesian elementary schools. These findings support constructivist learning theories and provide empirical evidence for PBL implementation within the Independent Curriculum framework. Future research should employ larger samples and controlled designs to strengthen generalizability across diverse educational contexts.